A cohort integration analysis of work and education participation among internal mobile and non-mobile immigrants by reason for immigration - Lasse Sigbjørn Stambøl (European Regional Science Association (ERSA), 2016)
Abstract: The aim of the paper is to analyse immigrants' participation versus non-participation in the regional labour markets and/or in education. For comparison we have followed groups of immigrants by their reason for immigration, like refugees, labor-, family- and education-immigrants and Nordic immigrants with special focus on those who do not move domestically between labor market regions versus those who make such regional relocations. We investigate whether migration contribute to change the labor market status of immigrants using a 'cohort-analysis', where we follow selected arrival cohorts of immigrants through some years after they immigrated for the first time. The investigation is a 'two-way analysis', dependent on each immigrant's initial labor market status. For those who are not active in any job or education, we analyze their probability of entering any activity statuses, and for those already in activity, we analyze their ability to maintain their activity status. Both dimensions are important for the immigrants' level of integration. The analysis is based on micro panel data measured by means of a complete annual regional vacancy account for each of the years involved in the study. These data and methods allow us to specify each immigrant's annual labor market status, thus also each immigrant's annual change of labor market status. The results indicate that domestic migration is partial beneficial for immigrants to obtain employment or to carry out an education. The effect of relocation as the ease of access varies, however, according to the immigrants' reason for immigration. Immigrants who remain outside of employment and/or education is mostly to be found among refugees, family-immigrants and immigrants with unspecified reason for immigration, while education- and labor-immigrants and Nordic immigrants show the strongest tendency to enter a job or start an education. The main trend is that immigrants who move between labor market regions show a stronger tendency to enter activity statuses than immigrants who do not provide such removals, and is most beneficial for immigrants initially settled at lower centrality. Immigrants who are already in employment and/or education, the education- and labor-immigrants and Nordic immigrants show higher tendency to maintain such "activity statuses" than refugees, family-immigrants and immigrants with unspecified reason for immigration. The main trend is that immigrants who do not move between labor market regions show stronger tendency to remain in employment and/or education than immigrants who make such moves. Those who relocate are thus associated both with stronger tendency of finding a job or starting an education, but also more likely to quit their job or education.
Keywords: J61; 330; Employment; Education; Migration; Immigrants